A Sociolinguistic Exploration of Sociolects in Translation - Meriam BENLAKDAR (Altralang Journal, 2020)
ABSTRACT: Translation is not a mere transfer of words; it is a process that intersects with many other disciplines such as sociolinguistics whose object of study is the relationship between language use and society. Since sociolects are language variations of particular social groups, the present paper attempts to answer the question of how sociolects are translated when the source and target languages are completely different, which can prove to be quite problematic for translators. It argues that sociolects may not be properly translated without adopting a sociolinguistic approach to achieve cross-cultural communication. The study aims to provide further insights into the way English sociolects are translated taking into account several variables as well as paralinguistic and extralinguistic features. The framework within which this study is conducted is sociolinguistic theory of translation which will be applied to some sociolects.